Genetic structure of Malaysia Apis dorsata aggregations in Marang district (Terengganu) - Sahebzadeh, Najmeh; Adam, Nur Azura; Lau, Wei Hong; Mardan, Makhdzir; Abdul Ali, Manaf; Tan, Soon Guan (International Bee Research Association, 2013)
Apis dorsata is a major pollinator in the rainforests of Peninsular Malaysia, which is threatened by frequent harvesting via the removal of whole comb nests from trees during the harvesting season. There is an urgent need for conservation of this species and the long-term survival of tropical lowland forests. In this paper, the genetic relatedness of A. dorsata aggregations are addressed with a preliminary study on local populations in Malaysia. The analysis of 30 single locus DNA microsatellite markers on three aggregations at intra-aggregation level showed that the queens of different nests within an aggregation were significantly different and not related as mother-daughter (P > 0.063). At inter-aggregation level, the results demonstrated that there was no significant relatedness between the aggregations (P > 0.05) separated by a distance of 0.5 km. The results showed that adjacent aggregations were genetically different and had enough time for establishing the colonies to produce honey.